The Effect of Promotion and Job Training on Job Satisfaction of Employees: An Empirical Study of the SME Sector in Bangladesh - Md. Atikur Rahaman; Md. Sayed Uddin (Korea Distribution Science Association, 2022)
SME sector’s success also depends on its employees’ job satisfaction as satisfied employees are likely to be more productive at the workplace and positively enhance SME business performance. Small and medium firms are the heart of the economy, and employees are the main and valuable asset for the SME firms. If SME business managers can increase employee satisfaction, then SMEs’ performance will also increase in the future. Hence, the current study aims to determine the job satisfaction of SME employees by analyzing the impact of job training (JT) and promotion (PRO) opportunities on employee job satisfaction. Purposive sampling is applied in the study, and 202 SME employees have participated as sample respondents. The final sample size is n = 202. SPSS 26.0 version is used to analyze the hypotheses. The study findings show that both job training (JT) and promotion (PRO) have a positive effect on SME employee job satisfaction. It does indicate that SME managers need to provide necessary training programs and timely promotion to their current working employees to keep them satisfied with their job. Promotion and effective job training will certainly enhance employees’ job satisfaction. The study has also offered a few strategic implications for SME business managers.